Advertising Costs and Equilibrium–A Correction - Chamberlin, Edward H. (Review of Economic Studies, 1944)
Journal Article Advertising Costs and Equilibrium—A Correction Get access Edward H. Chamberlin Edward H. Chamberlin Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 12, Issue 2, 1944, Pages 116–120, https://doi.org/10.2307/2296097 Published: 01 September 1944